Congenital fetal leukemia causing fetal hydrops: diagnosis and perinatal Course - Huerta Sáenz, Igor (2014)
A case of leukemia in a 31-week fetus with severe anemia, hydrops and intrauterine death is reported. Ultrasound evaluation showed severe hydrops and anemia quantified by Doppler of the medial cerebral artery, as well as visceromegaly and renal enlargement with signs of dysplasia. There was fetal demise before other diagnostic tests could be performed. Labor was induced. Post mortem examination of the product determined fetal leukemia.